Political connections and firms' formalization: Evidence from Viet Nam - Duc Anh Dang; Hai Anh La (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The literature shows that political connections have different effects on firms' activities. However, the question of how political connections affect firms' formalization has not been explored. Using data from three waves of the Vietnam Small and Medium Enterprise Survey for the period from 2007 to 2011, this paper aims to examine the relationship between political connections and firms' formalization in Viet Nam. We find that firms with political connections increase their share of formal workers. The results also show that smaller firms tend to be more formalized if they have political connections. To overcome bias and inconsistency concerns due to potential omitted variables and reverse causality, we use political connections in a firm's industry in other districts as an instrumental variable. The instrumental variable results confirm our previous results that political connections do indeed lead to a higher level of formalization.
Keywords: D72; E26; 330; political connections; formalization; Viet Nam